2019
DOI: 10.1021/acs.nanolett.9b03517
|View full text |Cite
|
Sign up to set email alerts
|

Strongly Confined Excitons in GaN/AlN Nanostructures with Atomically Thin GaN Layers for Efficient Light Emission in Deep-Ultraviolet

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
46
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(53 citation statements)
references
References 35 publications
7
46
0
Order By: Relevance
“…For extremely thin III-Nitrides quantum wells and quantum disks, the quantum confinement effect is strong when the thickness is 1-3 atomic monolayers. [30][31][32][33][34][35] In our system, the thickness of each InGaN or AlGaN layer is measured to be 9 atomic monolayers or above, thick enough to neglect the spatial quantum confinement. Since the contrast of the HAADF-STEM images is highly dependent on the effective atomic number (Z), and elements with a higher Z appear brighter in the resulting image, [36] InGaN layers are brighter than the neighboring AlGaN layers in the GaN NR.…”
Section: Resultsmentioning
confidence: 99%
“…For extremely thin III-Nitrides quantum wells and quantum disks, the quantum confinement effect is strong when the thickness is 1-3 atomic monolayers. [30][31][32][33][34][35] In our system, the thickness of each InGaN or AlGaN layer is measured to be 9 atomic monolayers or above, thick enough to neglect the spatial quantum confinement. Since the contrast of the HAADF-STEM images is highly dependent on the effective atomic number (Z), and elements with a higher Z appear brighter in the resulting image, [36] InGaN layers are brighter than the neighboring AlGaN layers in the GaN NR.…”
Section: Resultsmentioning
confidence: 99%
“…In 2019, Shan et al reported the DUV laser emitting at 249 nm by optical pumping based on binary AlN/GaN heterojunctions, which was comparable to state-of-the-art AlGaN quantum well (QW) lasers at similar wavelengths 75 . In 2020, Toropov et al demonstrated an enhancement of the short-range electron–hole spin-exchange in GaN/AlN structure with the embedded single GaN well and reported the 2D exciton nature of light emission at temperatures up to 300 K with a possibly short emission wavelength 76 .…”
Section: Manipulation Of Fields Of Chemical Potentialsmentioning
confidence: 99%
“…This easy cleavage property is now extensively used by people working in the area of 2D materials and hBN is world-widely utilized as a passivation layer for different few-monolayer stacking of transition metal dichalcogenides, GaSe, InSe, black phosphorus, and so on [30,31]. Also of interest is the ultra-short emission wavelength at 215 nm which clearly sits at a wavelength substantially shorter than what can be achieved using the ultimate challenger heterostructure based on a gallium plane embedded into AlN barrier layers (235 nm at 8 K) [32]. Although a lot of efforts are at the time being focused towards the 260-270 nm range [33,34] where light absorption by DNA molecules is important, hBN-related devices will be of paramount importance for fully covering the 200-300 nm range for nucleic acids (DNA and RNA) where the UV absorbance is due to transitions of the planar purine and pyrimidine bases (see Figure 1 where the wavelengths that can be attributed to GaN-AlN devices are yellowed while the region of hBN-related ones is greyed) [35].…”
Section: The Early Daysmentioning
confidence: 99%
“…Advantage can be taken of this performance for DUV LEDs with operating wavelengths smaller than those reachable using conventional nitride, that is to say 235 nm [32]. hBN can be simultaneously used as an efficient material for light emission and a transparent one for light extraction in the context of a simple LED design based on a pn junction.…”
Section: Excitons In Hbn 51 Deep Ultraviolet Photoluminescence and Ementioning
confidence: 99%
See 1 more Smart Citation